Hubungan Riwayat Imunisasi Dasar Lengkap dan Riwayat Penyakit Infeksi dengan Kejadian Stunting pada Balita > 5 Tahun di Kota Depok Tahun 2023 - Afriansyah, Eddy; Fitriyani, Lia (Universitas Malahayati, 2023)
ABSTRACT Globally, the stunting rate in 2019 was 21.3% or around 144 million children under five in the world were stunted. The prevalence of stunting under five in Indonesia is 36.8%. The results of the 2022 Indonesian Nutrition Status Survey (SSGI) show that the prevalence of stunting in Depok City is 12.6 percent. To know the relationship between history of complete basic immunization and history of infectious diseases with the incidence of stunting in infants > 5 years in Depok City in 2023. The type of research used is analytic observational. The population in this study were all toddlers> 5 years. The population in this study were 3,675 toddlers > 5 years. The sample in this study was 400 toddlers > 5 years. The sampling technique in this study is probability sampling. Data collection using a questionnaire. In this study the analytical technique used was SPSS 25. Data analysis in this study was univariate analysis and bivariate analysis (chi square). There is a relationship between a history of complete basic immunization (p value = 0.042; OR95% CI = 1.508 (1.104-2.243)) and a history of infectious diseases (p value = 0.024; 1.579 (1.061-2.349)) with the incidence of stunting in infants > 5 years in Depok City. There is a relationship between a history of complete basic immunization and the incidence of stunting in infants > 5 years in Depok City, there is a history of infectious diseases with stunting in children > 5 years in Depok City. Keywords: Immunization, Infectious Diseases, Stunting ABSTRAK Secara global angka stunting pada tahun 2019 sebesar 21,3% atau sekitar 144 juta balita di dunia mengalami stunting. Prevalensi balita stunting di Indonesia sebesar 36,8%. Hasil Survei Status Gizi Indonesia (SSGI) tahun 2022 prevalensi stunting di Kota Depok sebesar 12,6 persen. Diketahuinya hubungan riwayat imunisasi dasar lengkap dan riwayat penyakit infeksi dengan kejadi stunting pada balita > 5 tahun di Kota Depok tahun 2023. Jenis penelitian yang digunakan adalah observasional analitik. Populasi dalam penelitian ini adalah seluruh balita > 5 Tahun. Populasi dalam penelitian ini sebanyak 3.675 balita > 5 Tahun.Sampel dalam penelitian ini adalah 400 balita > 5 tahun. Teknik sampling dalam penelitian ini adalah probability sampling. Pengumpulan data menggunakan kuesioner. Dalam penelitian ini teknik analisis yang digunakan adalah SPSS 25. Analisis data dalam penelitian adalah analisis univariat dan analisis bivariat (chi square). Ada hubungan riwayat imunisasi dasar lengkap (p value = 0,042; OR95% CI = 1,508 (1,104-2,243)) dan riwayat penyakit infeksi (p value =0,024; 1,579 (1,061-2,349)) dengan kejadian stunting pada balita > 5 tahun di Kota Depok. Ada hubungan riwayat imunisasi dasar lengkap dengan kejadian stunting pada balita > 5 tahun di Kota Depok, ada riwayat penyakit infeksi dengan kejadian stunting pada balita > 5 tahun di Kota Depok. Kata Kunci: Imunisasi, Penyakit Infeksi, Stunting